Comparative Analysis of WEEE Recovery Strategies and the WEEE Treatment Status in China and Romania. (2016) - Daniel, Lates; Sorina, Moica
Abstract: The growth of requirements on electrical and electronic equipment (WEEE) market in the world entails numerous consequences that are found in Romania and China. One of them is the increasing number of waste (WEEE) due to increased life, due to evolution of the technical process and to a wide range of equipment they produce. In terms of environmental pollution and changing of climate, this is a major problem due to toxic materials that are used in fabrication. So, WEEE is a common problem of Romania and China.